2019
DOI: 10.1111/medu.13950
|View full text |Cite
|
Sign up to set email alerts
|

Exploring researchers’ perspectives on authorship decision making

Abstract: Context Authorship has major implications for researchers’ careers. Hence, journals require researchers to meet formal authorship criteria. However, researchers frequently admit to violating these criteria, which suggests that authorship is a complex issue. This study aims to unpack the complexities inherent in researchers’ conceptualisations of questionable authorship practices and to identify factors that make researchers vulnerable to engaging in such practices. Methods A total of 26 North American medical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…40,41 In addition, findings from a study of research practices in medical education suggest that some of this growth in author team size may be related to questionable research practices like honorary authorship. 42,43 As the field of medical education continues to mature and its literature base grows, strategic selection of team members, including the rightsizing of the knowledge synthesis team, will become increasingly important. Thus, future research may be needed to further examine the composition and size of knowledge synthesis teams in order to provide evidence-based practical guidance on team construction.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 In addition, findings from a study of research practices in medical education suggest that some of this growth in author team size may be related to questionable research practices like honorary authorship. 42,43 As the field of medical education continues to mature and its literature base grows, strategic selection of team members, including the rightsizing of the knowledge synthesis team, will become increasingly important. Thus, future research may be needed to further examine the composition and size of knowledge synthesis teams in order to provide evidence-based practical guidance on team construction.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] These studies have also identified factors beyond ICMJE criteria that may influence authorship, including: reciprocity (e.g., to return a favor to someone who helped in some way in the past); feelings of loyalty or obligation, particularly to advisors or mentors; beliefs that the existing criteria do not take into account the important "minutiae of research beyond writing and data reduction"; 15 and institutional and social structures and hierarchies like tenure status, gender, and minority status. 2,11,15,[17][18][19][20][21] Despite guiding criteria, then, the social practice of authorship remains a contested one in that published criteria and enacted practice do not always align.…”
Section: I We and They: A Linguistic And Narrative Exploration Of The Authorship Processmentioning
confidence: 99%
“…Published 2020. This article is a U.S. Government work and is in the public domain in the USA 6 In these interviews, without prompt multiple participants veered away from the present to describe authorship experiences from their training. In recounting these experiences, which in some cases were decades old, the participants described instances in which they were excluded from manuscripts, relegated to an unexpected placement in author order, or pressured to add individuals that they felt did not warrant authorship.…”
Section: When I Read Cornett Et Al's Review 1 I Found the Concept Ofmentioning
confidence: 99%
“…Second, the impact of authorship experiences can be long‐lasting with reverberations across a researcher's career. In a recent qualitative study, my colleagues and I interviewed 26 junior and senior medical education faculty members in North America about their recent authorship experiences 6 . In these interviews, without prompt multiple participants veered away from the present to describe authorship experiences from their training.…”
mentioning
confidence: 99%
See 1 more Smart Citation